Pengaruh Budaya Organisasi, Kompetensi Karyawan Dan Komitmen Organisasi Terhadap Kinerja Karyawan Pada PT. Ciptatama Dimensi Prima - Juprianto; Winda Evyanto (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2024)
The purpose of this research is to explore the influence of organizational culture, employee competence and organizational commitment on employee performance at PT. Ciptatama Dimensi Prima. The population in this study were all employees of PT. Ciptatama Dimensi Prima, totaling 114 employees. The sample can involve all members of the population based on saturated sampling techniques. The data analysis process is carried out through a series of steps, including data quality testing, classical assumption testing, influence testing and hypothesis testing. The results of multiple linear regression analysis show that organizational culture has an influence of 16.0% on employee performance. Employee competency has an influence of 39.3% on employee performance. Organizational commitment has an influence of 30.7% on employee performance. In this context, analysis of the coefficient of determination (R2) confirms that the combination of organizational culture, employee competence and organizational commitment is able to explain as much as 57.1% of the variation in employee performance. The results of the t test and F test strengthen the findings that organizational culture, employee competence and organizational commitment have a positive and significant influence on employee performance at PT. Ciptatama Dimensi Prima, both partially and simultaneously.